HMGA2 and the p19Arf-TP53-CDKN1A axis: a delicate balance in the growth of uterine leiomyomas - Markowski, Dominique Nadine; von Ahsen, Inga; Nezhad, Maliheh Hashemi; Wosniok, Werner; Helmke, Burkhard Maria; Bullerdiek, Jörn (Genes, chromosomes & cancer, 2010)
Pathogenetically, uterine leiomyomas (ULs) can be interpreted as the result of a monoclonal abnormal proliferation of myometrial cells. Oncogene-induced senescence (OIS) is a frequent phenomenon in premalignant lesions that leads to a growth arrest mainly by the activation of two potent growth-inhibitory pathways as represented by p16Ink4a and p19Arf. The relevance of OIS for the development of UL has not been addressed, but HMGA2, encoded by a major target gene of recurrent chromosomal abnormalities in UL, has been implicated in the repression of the Ink4a/Arf (CDKN2A) locus. This prompted us to examine if HMGA2 contributes to the growth of leiomyomas by repressing this locus. Contrary to the expectations, we were able to show that generally ULs express significantly higher levels of p19Arf mRNA than myometrium and that UL with 12q14∼15 rearrangements showed higher expression levels than UL with other cytogenetic aberrations. Furthermore, the finding of a significant correlation between the expressions of p19Arf and CDKN1A shows that p19Arf triggers senescence rather than apoptosis in UL. Furthermore, the expression levels of HMGA2, p19Arf, and CDKN1A were found to be correlated with the size of the tumors, indicating that an enhanced growth potential is counterbalanced by the p19Arf pathway. Mechanistically, the UL may thus execute a program already present in their cell of origin, where it is activated to protect the genome, for example, in the case of enhanced proliferation. In summary, the results identify the p19Arf-TP53-CDKN1A pathway as a major player in the growth control and genomic stability of uterine fibroids. © 2010 Wiley-Liss, Inc.
Im Titel erscheint die Zeichenfolge "Arf" hochgestellt
Gesehen am 04.05.2023